Electrophoretic non-ionic nano-spheres (latexes) for structural coloring. (19th May 2017) - Mokude, Daiki; Takasu, Akinori; Higuchi, Masahiro
Abstract: Electrophoretic deposition (EPD) is one of the most important coating methods. This method has various advantages, such as being able to make a coating as a uniform film, even on a complex surface. Recently, we found that non-ionic poly(ester-sulfone) materials show anode selective electrophoretic behavior. In this paper, we performed electrophoresis of non-ionic nano particles (diameter: ca. 300 nm), prepared via soap-free emulsion copolymerization of vinyl monomers containing a sulfide linkage with styrene and subsequent oxidation to a sulfonyl group. After EPD, a structural color was observed, indicating that the monodisperse spheres had attached to the surface and exhibited specific light diffraction, in which the wavenumber is dependent on the incident angle. Graphical abstract: Highlights: The first example of electrophoretic non-ionic latexes. Coating of monodisperse latex for structural color.